2023
DOI: 10.1002/ajhb.24003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of catastrophic events on the sex ratio at birth: A systematic review

Lilybeth Fontanesi,
Maria Cristina Verrocchio,
Melissa D'Ettorre
et al.

Abstract: ObjectiveThe impact of maternal stress on birth outcomes is well established in the scientific research. The sex ratio at birth (SRB), namely the ratio of male to female live births, shows significant alteration when mothers experience acute stress conditions, as proposed by the Trivers‐Willard Hypothesis. We aimed to synthetize the literature on the relationship between two exogenous and catastrophic stressful events (natural disasters and epidemics) and SRB.MethodsA systematic search was run in Scopus, PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…It must be noted that the present study is not the only one that has failed to detect an effect of the stressful event on SRB. In the most recent systematic review of the effects of catastrophic events on the sex ratio at birth, out of the 25 eligible studies, sixteen of them found a decline in the SRB, three detected a rise in SRB, four did not detect any changes, and two studies detected contradictory results [40]. Grech [41] reviewed (and co-authored) several studies where no effect on SRB was found, possibly due to a small cohort size or the ability of the population to adapt to stressful events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that the present study is not the only one that has failed to detect an effect of the stressful event on SRB. In the most recent systematic review of the effects of catastrophic events on the sex ratio at birth, out of the 25 eligible studies, sixteen of them found a decline in the SRB, three detected a rise in SRB, four did not detect any changes, and two studies detected contradictory results [40]. Grech [41] reviewed (and co-authored) several studies where no effect on SRB was found, possibly due to a small cohort size or the ability of the population to adapt to stressful events.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies [21,22,43,44] used a simple cohort comparison approach wherein the exposed group was statistically compared with an unexposed one, usually in the past. This approach has been criticized because it does not take into account temporal trends, seasonal variations, or short-term fluctuations [40,45]. The time series approach used in this study can solve these issues, and although it is not without possible flaws [45], it is still preferable to a simple cohort analysis.…”
Section: Discussionmentioning
confidence: 99%